PERSEPSI MAHASISWA TENTANG EFEKTIVITAS PROGRAM PENGALAMAN LAPANGAN KEPENDIDIKAN (PPLK) TERHADAP KESIAPAN MENJADI GURU PADA MAHASISWA PENDIDIKAN EKONOMI UNP - Ira Fitria; Syamwil Syamwil; Rita Syofyan (Universitas Negeri Padang, 2018)
The purpose of this articel is to analyze the effect Perseption of students about Effectivity of The Educational Internship Experience Program (PPLK) towards the readiness becoming a teacher. This type of the research is descriptive quantitative. The population of research is the economics students July to December 2017 period. The sample is 40 students that be selected from total 66 students by using Slovin formula with Insidential Random Sampling technique. The data collected by using the questionnaire. The instrument t is tested by using validity and reliability test. The data is analyzed by using descriptive and inductive (inferensial) analyze which is the normality test, heteroscedasticity test, and hypothesis test is analyzed by using simple regression, determination coefficient and F experiment with α=0.05. The result of this research has showed that there has been a significant perseption of students about effectivity of the educational internship experience program PPLK to the readiness become a teacher, it has showed by the significant of 0,008 < 0,05 and TCR perseption of students about effectivity of PPLK variable (x) at 75,79%. Both TCR for variables of perseption of students about effectivity of PPLK and readiness become a teacher are determined in a good category. It has indicated that PPLK has contributed to the readness become a teacher. Based on the results of the study it is suggested that students are able to provide apperception the beginning of learning because with the provision of apperception the learning will be more directed and students must be able to adapt the new environment.Keywords: Perseption , Effectivity, Educational Experience Program , Readiness Becoming a Teacher